Karakteristik Fisikokimia Pati Ganyong (Canna edulis Kerr.) dan Garut (Maranta arundinacea) yang Dimodifikasi dengan NaOH-Etanol - Parwiyanti Parwiyanti; Malahayati N; Silalahi R (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Parwiyanti P, Malahayati N, Silalahi R. 2020 physicochemical characteristics of canna (canna edulina kerr.) and Arrowroot (Maranta arundinacea) starches modified by NaOH-Ethanol. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Modification of Canna edulis and Maranta arundinacea starch through NaOH-Etanol was conducted to improve and expand the use of this starch in food industry, especially instant product. The objective of this study was to study the effect of the amount of NaOH on physicochemical characteristics of modified canna and maranta starches. This research used a Split Plot Design (RPB) with the main plot of type of tuber (canna and maranta) and a plot of the amount of NaOH added (0, 3, 6, 9) grams per 10 grams of starch. The observed parameter were whiteness level, yield, swelling power and solubility index, cold water-solubility, water absorption index, moisture content and ash content. The results showed that the type of tubers and the amount of NaOH significantly affected the whiteness level, cold water solubility, water absorption index, and water content. Maranta starch modified with 9 g NaOH was the best treatment with the value of water absorption index (IAA) is 203.95%.